(untitled) (Quinto Sol, 2013)
This paper studies the role performed by parsons as ecclesiastical judges in the Buenos Aires rural parishes during the last colonial decades. For such purpose, we analysed the regulation relating to their functions in the judicial environment as well as the effective exercise of these tasks. Particularly three fields of action of these parishes-judges are considered: marital control, the administration of the right of “asilo en sagrado”, and their intervention in testamentary dispositions. The period in which we center the research is crossed by the tension that meant the reduction of competences carried out by borbonic policies. In response to these regalist measures, we will see clergymen either deprived of some judicial functions, keeping others, or resisting the reduction of some tasks that, until that moment, were in their hands. As it would happen in other areas, also in the excercise of justice, parishes and mayors will share some functions and –not unfrequently- will compete for the control of institutional power at local levels.